Zakat Literacy Level of Residents and Muhammadiyah Sympathists in Krajan Village - Hakim, Lukmanul; Adriansyah, Ikhwan (JURNAL AT-TURAS, 2023)
Krajan Village is a village with a majority Muhammadiyah population located in Banyumas Regency, however one of the institutions under the auspices of Muhammadiyah namely LazisMu Krajan Village is claimed to be in a passive condition, even though LazisMu Krajan Village as an institutional structure is under the auspices of LazisMu Banyumas Regency which is LazisMu with a myriad of achievements, starting from 2018 to 2022 Lazismu Banyumas Regency won several awards as the best amil zakat infak and shodaqoh institution at provincial to national levels. This phenomenon prompted researchers to measure the zakat literacy level of residents and Muhammadiyah sympathizers in Krajan Village and to measure the phenomena that affect the level of zakat literacy. The scope of this research lies in the residents of Krajan Village, Banyumas Regency, the majority of whom are Muhammadiyah sympathizers and members. This study uses a descriptive qualitative method with primary data obtained from interviews with Krajan Village residents who are classified as Muhammadiyah members and sympathizers regarding matters related to zakat literacy. The results of this study indicate that the level of literacy among Muhammadiyah residents and sympathizers in Krajan Village is still classified as poor in terms of knowledge and practice of zakat, this phenomenon is inseparable from the poor condition of LazisMu in Krajan Village, as evidenced by the poor management of the institution, to the minimal realization of the program. which then significantly affects the literacy quality of the citizens and Muhammadiyah sympathizers. The results of this study can be used as a general description of the literacy quality of the Krajan Village community to be used as a reference in improving professional institutional governance, and increasing the realization of programs for collecting, utilizing, and distributing zakat for LazisMu Krajan Village.